2018
DOI: 10.1039/c8ra06984k
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of cup-like ZSM-5 zeolite and its excellent oxidative desulfurization performance

Abstract: One-pot synthesis of small size cup-like hollow ZSM-5 single crystals and their oxidative desulfurization performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The 550 nm NENU-9 showed a significantly higher conversion of DBT (~90%) in 60 min compared to 300 μm NENU-9 (41%) and the homogeneous POM (2%) in 90 min. To further improve the stability of POM@MOF materials and their catalytic ODS performance, POM@MOF compounds were confined in other porous materials, e.g., MCM-41 [76,77], carbon nanotubes [78], mesoporous SBA-15 [79], and hollow ZSM-5 zeolite [80]. For example, POM@Cu-BTC was confined in the pores of MCM-41 to prevent deactivation of the catalyst [76].…”
Section: Oxidation Reactionmentioning
confidence: 99%
“…The 550 nm NENU-9 showed a significantly higher conversion of DBT (~90%) in 60 min compared to 300 μm NENU-9 (41%) and the homogeneous POM (2%) in 90 min. To further improve the stability of POM@MOF materials and their catalytic ODS performance, POM@MOF compounds were confined in other porous materials, e.g., MCM-41 [76,77], carbon nanotubes [78], mesoporous SBA-15 [79], and hollow ZSM-5 zeolite [80]. For example, POM@Cu-BTC was confined in the pores of MCM-41 to prevent deactivation of the catalyst [76].…”
Section: Oxidation Reactionmentioning
confidence: 99%
“…Numerous POM@MOF‐199@MCM‐41 catalysts have been prepared and tested, using Cesium or Cobalt ionic liquid modified POMs, surfactant‐type heteropolyacid, or employing different mesoporous supports such as ZSM‐5 and LZSM‐5 . Moreover, the use of a synthetic fiber based on cellulose acetate (CA), zinc oxide and polyvinylpyrrolidone (PVP) has also been tested as support for Co‐POM@MOF‐199.…”
Section: Mofs As Support Of Ods Active Speciesmentioning
confidence: 99%
“…Rafiee et al first synthesized three composites of POMs and MOF-199(Cu) and demonstrated their potential in ODS reactions [82]. Further, a series of such composites (including, but not limited to, POM@MOF-199@MCM-41, C-POM@MOF-199@MCM-41, HPA@MOF-199@CA, CNTs@MOF-199-Mo 16 V 2 ) were prepared for ODS reactions with O 2 as the oxidant [83][84][85][86][87][88][89][90][91]. The catalytic results indicated that the combination of POM and MOF-199(Cu)@MCM-41 might be helpful for the enhancement of ODS performance under the reaction condition of O 2 as the oxidant.…”
Section: Composites Of Mofs and Polyoxometalatesmentioning
confidence: 99%